Implementation Analysis of Curriculum 2013 Towards Interactive Learning Aspects and Multimedia-Based Learning - Diah Ayu Lestari; Sutrisno Sutrisno (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This research aims to determine the application of interactive and multimedia-based learning which conducted by the teachers from office administration in state vocational high school 2 Blitar. This research is qualitative research then the subjects are the teachers’ expertise of administrative programs, vice principal of curriculum and students. Data collection techniques used observation, interviews, and documentation. The results of this research are (1) interactive learning have been implemented, (2) Multimedia-Based learning has been implemented, but it is needed for developing the multimedia which used for teaching process.It can be seen that the teacher conducts learning in accordance with interactive learning indicators. The implementation of the curriculum 2013 for aspects of multimedia-based learning has been carried out by teachers by implementing learning that contains multimedia-based learning indicators.